2016
DOI: 10.1556/036.103.2016.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sex and menstrual cycle in women on starting speed, anaerobic endurance and muscle power

Abstract: The aim of our study was to compare the indicators of starting speed, anaerobic endurance and power in women as well as men, and to investigate whether the values of these indicators differ in women during the follicular and luteal phases of the menstrual cycle. The studied group included 16 men and 16 women. The subjects performed the 20-second maximal cycling sprint test. The men performed the test twice at 14-day intervals. The women undertook the test 4 times: twice during the middle of follicular phase an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 14 publications
2
34
0
4
Order By: Relevance
“…Also, some authors suspect that differences in sarcomeral metabolism might have an influence on divergence in muscle power between sexes (27). Similarly to recently published results (28,29), the difference in anaerobic power parameters in women concerning menstrual cycle phases was not observed in our paper.…”
Section: Discussionsupporting
confidence: 84%
“…Also, some authors suspect that differences in sarcomeral metabolism might have an influence on divergence in muscle power between sexes (27). Similarly to recently published results (28,29), the difference in anaerobic power parameters in women concerning menstrual cycle phases was not observed in our paper.…”
Section: Discussionsupporting
confidence: 84%
“…When studies conducted were examined, it was stated by various authors that menstrual period did not increase or decrease performance (Jaffre et al, 2006;Uçdağ, 2011;Aras et al, 2016). In their study, Wiecek at al. (2016) reported that hormonal changes in the middle of follicular phase and luteal phase during menstrual cycle did not affect women in terms of anaerobic performance, while in another study it was reported that menstrual cycle did not influence peak power, average power and lactate intensity (Tsampoukos et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…In our research, we stated that anaerobic exercise causes a smaller increase in XO activity in people with higher anaerobic performance ( Wiecek et al, 2017a ). At the same time, it is known that men generate greater anaerobic power and have higher anaerobic capacity than women ( Wiecek et al, 2015b , 2016 ).…”
Section: Introductionmentioning
confidence: 99%